Endangered - Schrefer, Eliot, 1978- (Scholastic Press, 2012)
A girl, having travelled with her mother to an animal sanctuary for bonobos in the Congo, struggles to survive with the animals after revolution breaks out and she and the chimpanzees are forced to flee into the jungle.